Electrochemical investigations on CO2 reduction mechanism in molten carbonates in view of H2O/CO2 co-electrolysis. (21st April 2021) - Meskine, H.; Albin, V.; Cassir, M.; Ringuedé, A.; Lair, V.
Abstract: In order to reduce carbon dioxide emission, one solution is to convert into valuable chemicals or fuels, e.g. transforming CO2 into CO by electrochemical reduction. Thus, this greenhouse gas could be re-used in particular as syngas (CO + H2 ) by co-electrolysis of CO2 /H2 O. High temperature electrolysis cells can be the best energetic devices to produce such syngas. In particular, molten carbonates are known to solubilize CO2 very significantly higher than other solvents. Therefore, it is compulsory to investigate and understand the mechanism of CO2 reduction in such media to consider its further use and valorisation. The present study is a critical approach aiming at elucidating the mechanisms for CO2 electroreduction, using an inert Pt electrode in the molten eutectic Li2 CO3 –K2 CO3 (62-38 mol%), at 650 °C, under different partial pressures of CO2 . Complementary electrochemical techniques, including sweep square-wave voltammetry and relaxation chronopotentiometry, were carried out. Their combination allowed us to evidence that the electroreduction of CO2 into CO is feasible in oxo-acidic conditions, involving a diffusion-limited quasi reversible system in a one electron-step. Highlights: Electrochemical reduction of CO2 was investigated in molten carbonates. In oxoacidic conditions (P (CO2 )> 0.1 bar), CO2 is reduced into CO. It is diffusion-limited, with a one-electron step, before chemical reaction to CO. CO formed is first adsorbed before being desorbed, solubilized and released as gas.